Inventory Management and Accounting System for Fruit Traders in Traditional Market in Sayan Village, Ubud Gianyar District: Agribusiness Perspective - Made Satria Wibawa; Ni Kadek Sri Utari (Journal of World Science, 2025)
In an agribusiness system involving agricultural supply chains, inventory recording is one of the economic resources that plays an important and strategic role, especially for the fresh fruit marketing chain, which is vulnerable to damage. Inventory is the main current asset for fruit traders in traditional markets with fast cash flow. This condition requires traders to manage and record inventory properly to maintain business continuity and minimize losses caused by damage or rotting of fresh fruit. However, in practice, fruit traders in the traditional market of Sayan Village have difficulty managing inventory, especially related to unorganized inventory accounting records. The purpose of this study was to analyze the inventory accounting system of fruit stall traders in the traditional market of Sayan Village, Ubud District, Gianyar Regency. This study uses a quantitative descriptive approach. Data collection was carried out through a survey technique with interviews of 3 respondents, who were determined by purposive sampling. The results showed that all fruit traders selling at fruit stalls in the traditional market of Sayan Village do not record inventory accounting. This results in difficulties in determining the amount of merchandise at the end of the accounting period and calculating gross profit. To make more accurate records and improve the efficiency of agricultural businesses, traders are advised to implement a periodic inventory recording system and conduct inventory assessments using the FIFO method.